AI-Driven Sustainability: Persepsi HR dan Karyawan terhadap Otomatisasi Ramah Lingkungan dalam Praktik SDM - Burhanuddin, Burhanuddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This qualitative study explores the perceptions of HR professionals and employees toward AI-driven sustainability in human resource practices within startup companies in Makassar, Indonesia. Through in-depth interviews and thematic analysis, the research reveals that while AI adoption offers significant potential for enhancing environmental sustainability, such as paperless recruitment and energy-efficient operations, its implementation faces challenges including budget constraints, workforce resistance, and gaps in digital literacy. The findings highlight a generational divide in technology acceptance, with younger employees more receptive to AI tools than their senior counterparts. Organizational culture and leadership commitment emerge as critical factors in successful integration. The study underscores the need for contextualized strategies that balance technological innovation with human-centric approaches, suggesting pilot projects, continuous training, and cross-sector collaboration as pathways to sustainable AI adoption in resource-limited settings.